2020
DOI: 10.1155/2020/1019872
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effectiveness of Pelvic Floor Muscle Training (PFMT) and Extracorporeal Magnetic Innervation (ExMI) in Treatment of Stress Urinary Incontinence in Women: A Randomized Controlled Trial

Abstract: Objective. The purpose of this study is to assess the effectiveness of pelvic floor muscle training and extracorporeal magnetic innervation in treatment of urinary incontinence in women with stress urinary incontinence. Methods. The randomized controlled trial enrolled 128 women with stress urinary incontinence who were randomly allocated to either one out of two experimental groups (EG1 or EG2) or the control group (CG). Subjects in the experimental group 1 (EG1) received 12 sessions of pelvic floor muscle tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 20 publications
0
58
0
1
Order By: Relevance
“…In such cases, it is a preferable activation of PFM to fully use the potential of the female pelvic floor. Recent studies [112,116,122] suggest that MS induces improvement in the severity of incontinence (level of evidence: 2); however, EAU does not recommend using magnetic stimulation to treat UI (strong evidence) and they do not mention vibration training [103]. EAU guidelines do not include the latest RCT work indicating the effectiveness of the above techniques in reduction of UI symptoms, these works are presented in this review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In such cases, it is a preferable activation of PFM to fully use the potential of the female pelvic floor. Recent studies [112,116,122] suggest that MS induces improvement in the severity of incontinence (level of evidence: 2); however, EAU does not recommend using magnetic stimulation to treat UI (strong evidence) and they do not mention vibration training [103]. EAU guidelines do not include the latest RCT work indicating the effectiveness of the above techniques in reduction of UI symptoms, these works are presented in this review.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect of MS was also noted in the reduction of UI incidents in patients after radical hysterectomy due to cervical cancer [114]. Moreover, it also causes short-and long-term improvement in the quality of life of women with SUI [115] while improving the severity of depression symptoms observed in these women [106,116]. It is also important to highlight the findings of Koh et al [108] who showed comparable efficacy of Extracorporeal Magnetic Innervation (ExMI) as alpha-blocker monotherapy in the treatment of female bladder outlet obstruction.…”
Section: Magnetic Stimulationmentioning
confidence: 95%
See 1 more Smart Citation
“…We added eleven additional questions about demographics, nine questions about risk factors, four questions regarding social/physical limitations from the King's Health Questionnaire [14], six questions regarding cultural aspects, and three questions about help-seeking behaviors to the target population. We measured the height and weight of participants to calculate their body mass index (BMI).…”
Section: Methodsmentioning
confidence: 99%
“…Still, more evidence is needed about the best timing of PFMT in the postpartum period [ 25 ]. There are also some methods that were useful in treating middle-aged women with UI or POP symptoms; however, their effect on prepartum and postpartum women is unknown, for example extracorporeal magnetotherapy [ 76 ].…”
Section: Discussionmentioning
confidence: 99%